Tourism Adaptation Strategy During the Crisis from Covid-19 Pandemic at Ngoi District, Luang Prabang Province: https://doi.org/10.69692/SUJMRD100126 - XAYAVONG, Somkhuan; LATTANASOUVANHNAPHONH, Champa; SISAVANH, Orlathai; SOULIYASACK, Somkhit; MIXAYKONE , Khanthaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study is about " Tourism adaptation strategy during the crisis from Covid-19 pandemic at Ngoi district, Luang Prabang Province" was studied in a qualitative format with an interview questionnaire as a tool for data collection. The results of the study found that the state of tourism in Ngoi City during the spread of the Covid-19 disease in Ngoi District is that tourists have dropped to 99.15%. Ngoi by training personnel and open the reception of tourists in the green tourism area and speed up the implementation of Lao safe tourism standards, most of the businesses that provide tourism services have closed their businesses by turning from the service business to farming and raising animals and starting to reopen in December 2021 and the local people are turning from the service profession to tourism to agriculture. raise animals and collect forest products of Dong, from the analysis of the tourism environment of Ngoi District and found that Ngoi District has strengths that can cope with this crisis situation more than weaknesses and there are also favorable opportunities from the external environment that can restore and develop the tourism situation in Ngoi District to normal people quickly. The use of corrective strategy (WO Strategy), the use of defensive strategy (ST Strategy) and the use of receiving strategy (WT Strategy) so that stakeholders in Ngoi district can adapt to the situation.